The Influence of Pro Evolution Soccer Game-Based Learning on Understanding Football Rules among Tenth Grade Students - Irvan Abdillah; Samsuddin Siregar; Rafael Burgueño; Felisa Romo Lea; Gertude Barton (Inspiree)
The  purpose  of  the study. This research endeavors to examine the influence of Pro Evolution Soccer on the understanding of Soccer regulations among tenth-grade students at SMA Dharma Pancasila Medan.